ISEB (INSTITUTO SUPERIOR DE ESTUDOS BRASILEIROS): A DIMENSÃO PEDAGÓGICA DA AÇÃO IDEOLÓGICA DE UMA INSTITUIÇÃO CULTURAL DO PERÍODO DE 1955 A 1964 - Soares, Silvia Leticia Marques (2014)
The decade of 1950 was marked by countless transformations, social, political and economic, arising from industrialization underway in Brazil. Some sectors of society, such as the political elites and a group of intellectuals, who felt the need to think about the educational policies understanding the educational process as a key dimension of the Brazilian reality through publications of many jobs. Thus, was created in july 14, 1955, the ISEB (Superior Institute of Brazilian Studies), still in government Cafe Filho, but started its activities in the command of Juscelino Kubitschek. It was an institute attached to the Ministry of Education and Culture (MEC), but enjoyed administrative autonomy and its members had freedom of research. It had intended to be a place of studies and debates to discuss the development of Brazil. Reflections were oriented to the realm of Social Sciences such as: Economics, Philosophy, Sociology, History and Politics, and from them, he sought to introduce the debate, dialog with the society through lectures on important institutes in season and yet, conferences in São Paulo, sponsored by the Center of the Federation of Industries (FIESP). His main works were: the publication of books, articles, newspapers and the holding of conferences, in addition to São Paulo, in other cities, such as Brasilia and Rio de Janeiro. By being composed of intellectuals of different ideological strands have emerged many clashes of ideas, which, consequently, has caused several crises within the institute. Some, such as Helio Jaguaribe, argued that the introduction of a process of development would like toward the industrial bourgeoisie. In view of the foregoing, this research investigated the educational role of the Institute, through the analysis of its publications and the courses he taught. The proposal if he gave in order to understand its two moments: the first, during the government of Juscelino Kubitschek, and the second, in the government of Joao Goulart, seeking to qualify ideological and pedagogically each one of them. The study showed that the Institute had a pedagogical dimension which, in spite of not being described in its bylaws, it was implicit in their publications, courses and lectures.